DONASI DAN BHAKTI SOSIAL BAGI MAHASISWA DAN TENAGA KEAMANAN TERDAMPAK COVID 19 (UPAYA MEMUTUS MATA RANTAI WABAH COVID 19) KEDUA - Rafika Ratik Srimurni, Rafika Ratik Srimurni; Iwan Satriyo Nugroho, Iwan Satriyo Nugroho; Abdussalam, Abdussalam; Jiehad Akbar Pria Utama, Jiehad Akbar Pria Utama; Guntur, Guntur; Musyfiq Amrullah , Musyfiq Amrullah; Fifi afiania, Fifi afiania (Media Nusantara, 2021)
Covid 19, students and lecturers who cared about this started carrying out donation activities for UNINUS students and employees who were affected. The students affected are students who live in boarding houses. Employees are campus security personnel/security units (security guards). Nusantara Islamic University would certainly be better in carrying out activities if it had partners from the community who were invited and willing to work together and contribute to the implementation of these donation and social service activitieNusantara Islamic University and the Nahdlatul Ulama Islamic Economics College, Subang, of course, in carrying out activities, it would be better if they had partners from the community who were invited and willing to work together and contribute to the implementation of this donation and social service activity. In this activity, UNINUS contacted a partner company, namely PT. HM Sampoerna TBK, which is well known for its concern and consistency in carrying out social service charity activities in the context of Corporate Social Responsibility, both institutionally and individually. PT HM Sampoerna TBK has a very high level of concern for the community and the environment, this development is proof of how multinational private companies can collaborate with higher education institutions in caring mutual cooperation in reducing the impact of the Covid 19 outbreak UNINUS also collaborates with the Nahdlatul Ulama Islamic Economics College, Subang with one of the social organizations under the Ministry of Defense (KMENHAN), namely the State Defense Forum (FBN) West Java Regional Leadership Council (DPW).